Inductive logic programming : 26th International Conference, ILP 2016, London, UK, September 4-6, 2016, Revised selected papers /: 26th International Conference, ILP 2016, London, UK, September 4-6, 2016, Revised selected papers. (2017) - Unknown
No abstract available